Human cytomegalovirus glycoprotein B inhibits migration of breast cancer MDA‑MB‑231 cells and impairs TGF‑β/Smad2/3 expression - Yang, Rui; Liang, Jie; Xu, Guo-Xiong; Ding, Liu-Mei; Huang, Hong-Mei; Su, Qi-Zhu; Yan, Jing; Li, Yun-Chun (Oncology letters, 2018)
Breast cancer is a leading cause of cancer‑associated mortality in females worldwide and evidence suggests that human cytomegalovirus (HCMV) infection may be implicated in the progress of breast cancer. HCMV glycoprotein B (gB) is the most abundant envelope protein and serves an important role in host cell entry. The present study aimed to clarify the role of HCMV gB in breast cancer cells.